Implementasi Algoritma Apriori Dalam Memberikan Rekomendasi Buku Pada Perpustakaan Smk Karya Guna 2 Bekasi - Haryono (LPPM STMIK IKMI Cirebon, 2024)
The library is one of the facilities provided by SMK Karya Guna 2 Bekasi. Some of the collection of books can be borrowed brought home, however there are also only accessible place. By using the apriori algorithm, can perform a search pattern such a high-frequency activities that often appear simultaneously using the technique of association rule. Because of the apriori algorithm uses a technique of association rule. So there are a lot of algorithms related such as apriori algorithm, FG Growth, CT-Pro, Improved a Priori, and others. However the disadvantages of apriori algorithm which is where the apriori algorithm is to perform scanning over and over. By using the apriori algorithm, can perform a search pattern such a high-frequency activities that often appear simultaneously using the technique of association rule. So it is easier for the officer of the library in recommends using a search pattern frequency books are often borrowed.